2022
DOI: 10.1007/s10644-022-09405-4
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Covid-19 on economic recovery: empirical analysis from China and global economies

Abstract: This research aims to utilize quarterly global VAR data from April 1, 2020, to September 30, 2021, to assess the influence of the economic recovery of China following the COVID-19 outbreak on global economies. China is one of the first big economies globally to show indications of recovery following the COVID-19 pandemic. The nation's economic growth has the biggest long-term influence on middle-income nations (0.17%) followed by low- and middle-income economies (0.16%) and high-income economies (0.16%) (0.15%… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 47 publications
0
5
0
Order By: Relevance
“…The Armington condition is satisfied between the two, as there is imperfect substitution between imports and domestic products. Gross domestic output is sold domestically and abroad under the profit maximisation principle, and producers choose between the domestic market and exporting, using a fixed constant elasticity of transformation (CET) function for the combination ( Zhang et al, 2022a ).…”
Section: Methodology and Data Sourcesmentioning
confidence: 99%
See 1 more Smart Citation
“…The Armington condition is satisfied between the two, as there is imperfect substitution between imports and domestic products. Gross domestic output is sold domestically and abroad under the profit maximisation principle, and producers choose between the domestic market and exporting, using a fixed constant elasticity of transformation (CET) function for the combination ( Zhang et al, 2022a ).…”
Section: Methodology and Data Sourcesmentioning
confidence: 99%
“…At the beginning of the COVID-19 pandemic, to control the spread of the virus, many countries adopted mandatory restrictions, such as social distancing, closures, quarantines and restrictions on production activities, which severely damaged global socio-economic operations ( Dong et al, 2022 , Nicola et al, 2020 , Xu and Wei, 2021 ). These restrictions led to significant changes in energy consumption and CO 2 emissions ( Shan et al, 2021 , Zhang et al, 2022a ). During COVID-19 restrictions, people spent more time working from home and engaging in online activities more frequently, which reduced the CO 2 generated by social mobility, such as commuting or travelling outside of the home ( Zhou et al, 2020 ).…”
Section: Introductionmentioning
confidence: 99%
“…A number of scholars have found that the transfer payment policy for ecological functional areas increases the efficiency of a region's green economy, improves the quality of its ecological environment, and promotes the development of a regional green economy (Chen et al, 2021, 2023; Yang, 2023). However, some studies have shown that transfer payments provided by the central government to resource‐exhausted cities can exacerbate haze pollution in local cities, as well as limit technological innovation and high‐tech industrial agglomeration (Yang et al, 2023).…”
Section: Literature Reviewmentioning
confidence: 99%
“…In addition to this, vertical transfers enable the central government to better control local governments' spending behavior. The central government regulates and restrains the expenditure behavior of local governments through the assessment and accountability mechanism for the use of transfer funds (Yang et al, 2023), and reduce the information asymmetry in the principal–agent problem, thus optimizing and increasing the allocation and transparency of local governments' fiscal expenditures, respectively. Therefore, the vertical transfer system can help local governments optimize the structure of fiscal expenditure, thus promoting the high‐quality development of the local economy.…”
Section: Research Hypothesesmentioning
confidence: 99%
“…(2022) develop a CGE model to evaluate the effect of government interventions in response to COVID-19 on production, final demand, and disposable income in Sardinia, Italy. Using vector autoregressive (VAR) models, Zhang et al. (2022) and Zhou et al.…”
Section: Introductionmentioning
confidence: 99%